Analysis of interaction between a configurable stone and a water flow - Strutinskiy, Vasiliy; Yakhno, Oleg; Machuga, Oleg; Hnativ, Ihor; Hnativ, Roman (Eastern-European Journal of Enterprise Technologies, 2018)
Erosion and destruction of riverbeds, foundations of flooded engineering structures are accelerated during natural phenomena, accompanied by a significant increase in the rate and wetted perimeter of river flows, the acquisition of mobility by the riverbeds’ particles. We have analyzed the interaction between a water flow and a separate stone of spherical, cylindrical, pyramidal, and other configurations. In particular, we have further developed a traditional approach to determining the force action of fluid on a solid barrier, a stone, for the case of compression of a water jet and taking into consideration the relative flow around a stone with the predefined geometrical characteristics: diameter, volume, and configuration. It has been proposed to employ the following parameters for interaction between the flow of water and rocks of various configurations: a compression ratio and a streamline coefficient. We have derived analytical dependences of the flow rate limit, which sets a stone into motion, its weight, and configuration. For spherical smooth stones these ratios are identical with the classical results. The coefficients, introduced for consideration, were categorized, depending on the configuration of a single stone, in tables and charts, which is convenient to apply when calculating bankprotecting structures. It has been proposed to use a stone shape factor, which is the ratio of the actual flow rate limit, enabling the mobility of a stone of arbitrary configuration taking into consideration its streamlining, to the flow rate limit of a spherical stone of the same mass with a reduced diameter. A shape factor should be applied as an adjustment multiplier in the calculation of the minimum mass of stones for bankprotecting structures and during hydroengineering works. For the wedgeshaped stones a value of the adjustment coefficient can sometimes amount to 0.170, which indicates high efficiency of applying such stones compared to those of spherical shape. In addition, the proposed coefficient could be used to refine the water flow rate limit in terms of loss of stability by existing bankprotecting structure. We have identified directions for further studies: analysis of the impact interaction between configurable stones and elements of bankprotecting structures; determination of motion parameters for waterstone flows